The nuclear receptor gene SfE75 regulates the molting of Sogatella furcifera - Wang, Yi-Ming; Wang, Yan-Yu; Gong, Ming-Fu; Zhang, Shi-Yan; Chen, Jiang-Ling; Li, Xin; Zhou, Cao; Yang, Hong (Journal of Asia-Pacific entomology, 2025)
[Display omitted] •Buprofezin and 20E regulate the transcription of SfE75 in Sogatella furcifera.•Knockdown of SfE75 causes molting failure and high mortality in nymphs.•SfE75 can regulates chitin synthesis and degradation.•The authors declare no conflict of interest. Ecdysone plays a crucial role in the process of insect moult development. The nuclear receptor gene E75, an early ecdysteroid response gene, plays a pivotal role in insect moulting. In this study, the nuclear receptor gene SfE75 was identified in Sogatella furcifera. The expression level of SfE75 was significantly reduced in the third instar S. furcifera under buprofezin treatment, while it was significantly increased in first-day fifth-instar nymphs after 12 h under 20E treatment. Silencing SfE75 in first-day fifth-instar resulted in delayed development and moult failure of the S. furcifera, with a significant increase in mortality and 23.39 % of the population surviving on the sixth day. Furthermore, the silencing of the SfE75 significantly inhibited the transcription levels of chitin synthesis and degradation. These results indicate that SfE75 is a key gene in the growth and development of S. furcifera by regulating the moulting via affecting the chitin synthesis and degradation. These findings elucidate the function of the SfE75 gene in the growth and development of the S. furcifera and and lay the foundation for subsequent studies on RNAi control strategies.